2012
DOI: 10.1186/1478-4505-10-25
|View full text |Cite
|
Sign up to set email alerts
|

Physicians in private practice: reasons for being a social franchise member

Abstract: BackgroundEvidence is emerging on the cost-effectiveness, quality and health coverage of social franchises. But little is known about the motivations of providers to join or remain within a social franchise network, or the impact that franchise membership has on client volumes or revenue earnings.Methods(i) Uncontrolled facility based of a random sample of 230 franchise members to assess self-reported motivations; (ii) A 24 month prospective cohort study of 3 cohorts of physicians who had been in the franchise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…The results of this study support evidence from several other settings that has shown that the longer-term benefits of franchising are often elusive, and even when they do accrue, providers are more focused on the immediate, proximate, benefits of membership [ 7 - 9 ]. Training and subsidies are highly rated by providers not because they are more valued than other benefits, but because other benefits are often so difficult to discern [c.f.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The results of this study support evidence from several other settings that has shown that the longer-term benefits of franchising are often elusive, and even when they do accrue, providers are more focused on the immediate, proximate, benefits of membership [ 7 - 9 ]. Training and subsidies are highly rated by providers not because they are more valued than other benefits, but because other benefits are often so difficult to discern [c.f.…”
Section: Discussionsupporting
confidence: 81%
“…Less attention has been given to provider and client experiences with or perceptions of franchising, factors that are also likely to influence the impact of this delivery model. The few studies that have addressed provider motivations to join or maintain membership in a franchise network have found that providers cite a number of factors, including access to medicines [ 7 - 9 ], social responsibility [ 7 - 9 ], technical improvement [ 7 - 10 ], improved client relationship management [ 11 ] and opportunities for networking [ 7 , 9 ]. There is limited evidence regarding the effect of franchising on service utilization [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective cohort study in Myanmar showed increasing monthly client volume for family planning services for the first 4-years after joining a franchise network. Client volume also increased for child health services [32]. Another prospective study in Vietnam found franchise membership increased total client volume by 40%, and use of reproductive health services by 51% [33].…”
Section: Resultsmentioning
confidence: 94%
“…In fractional franchise networks the quality and price controls only affect the franchised services while providers can use the franchise brand name to draw customers to the full range of services offered. In Myanmar providers who joined a franchise network increased their income; largely by increasing the number of clients accessing non-franchised, and therefore non-price controlled, services [32]. Future research into the effects of franchising on the price of health services, as well as how this shapes who accesses social franchise services may enable programs to achieve greater progress towards their equity goal.…”
Section: Discussionmentioning
confidence: 99%